Blockchain and AI The Intersection of Trust and Intelligence - Chowdhury, Niaz (Smart Technology Series, 2024)
In the rapidly evolving landscape of the digital age, two technologies stand out for their transformative potential: Artificial Intelligence (AI) and Blockchain. This book offers an incisive exploration of the confluence between these technological titans